End Suction Centrifugal Pump Operating in Turbine Mode for Microhydro Applications. (19th March 2014) - Ismail, Mohd Azlan; Othman, Al Khalid; Islam, Shahidul; Zen, Hushairi
Abstract : This paper reviews the current research works on the end suction centrifugal pump coupled with induction generator running in turbine mode for microhydro application. The information can be used by practicing engineers, researchers, and plant managers to understand the potential of pump running as turbine. Review on experimental and simulation works was carried out encompassing end suction single stage low specific speed which is less than 10 kW. This is followed by review of their efficiency improvement through modifications. The results show that centrifugal pump can operate in turbine modes without any modification on mechanical components. However, to achieve the best efficiency point (BEP), it requires higher flow rate and head than pumping rating. Efficiency improvement is viable through geometric modification to improve hydraulic characteristic. The studies also show that pump as turbine (PAT) can be directly coupled with modified induction motor as generator by adding capacitor and electric control system, regulating voltage and frequency at the output terminal. It was found that PAT offers the best low cost solution for microhydro application especially for third world countries that do not have local microhydro manufacturer.